EVALUATION OF THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS AND THEIR IMPACT ON FINANCIAL STABILITY-AN APPLIED STUDY OF A SAMPLE OF JORDANIAN COMMERCIAL BANKS FOR THE PERIOD 2012-2021 - Ahmed Rashid Ajrash; Kamel mmdoh kamel; Abdullah Mhaimeed Hawas (Scholars Digest Publishing, 2023)
The purpose of the study is to find out the impact of assessing the financial performance represented by (liquidity index, leverage index) on the financial stability represented by (Z-SCORE). The research sample included (6) commercial banks from 2012 to 2021 to collect the main data in order to measure the research variables and their dimensions. Using correlation and regression models in statistical software. (SPSS) to examine the relationships and influences between these variables and dimensions. The study concluded that the evaluation of financial performance represented by the financial leverage index has an impact on financial stability (Z-SCORE), while it found that the liquidity index represented by the employment ratio has no effect on financial stability such as the cash balance ratio, which had the greatest impact. The study presented several recommendations, the most important of which is that the efforts of banks should focus on maximizing the wealth of owners, motivating them and ensuring that they continue to invest in ways that support the economic activity of the state in a way that enhances financial stability. Banks should seek to attract long-term deposits or bonds and long-term loans in addition to using the latest financing methods. To achieve a stable financing structure and maintain a reasonable leverage ratio, such as secured investments, and to benefit from securitization operations and other non-depositary financing sources to maximize profits and increase financial stability.
Keywords: evaluation of financial performance, financial stability, Jordanian commercial banks.